The evolution of recombinant thrombolytics: Current status and future directions. Issue 4 (4th July 2017) - , Adivitiya; Khasa, Yogender Pal
ABSTRACT: Cardiovascular disorders are on the rise worldwide due to alcohol abuse, obesity, hypertension, raised blood lipids, diabetes and age-related risks. The use of classical antiplatelet and anticoagulant therapies combined with surgical intervention helped to clear blood clots during the inceptive years. However, the discovery of streptokinase and urokinase ushered the way of using these enzymes as thrombolytic agents to degrade the fibrin network with an issue of systemic hemorrhage. The development of second generation plasminogen activators like anistreplase and tissue plasminogen activator partially controlled this problem. The third generation molecules, majorly t-PA variants, showed desirable properties of improved stability, safety and efficacy with enhanced fibrin specificity. Plasmin variants are produced as direct fibrinolytic agents as a futuristic approach with targeted delivery of these drugs using liposome technlogy. The novel molecules from microbial, plant and animal origin present the future of direct thrombolytics due to their safety and ease of administration.